Epidemics between Qadr and Ḥadhar: Insights from al-Nawawī - Muhsin, Sayyed Mohamed; Muhammad, Murshid (International Islamic University Malaysia, 2021)
Being a great jurist and influential scholar with seminal works on hadith, theology, biography and jurisprudence, al-Nawawī’s (d. 1277) views on epidemics are of great significance in these days of the pandemic. This article explores his views and explanations vis-à-vis epidemic to find his perspectives on balance between qadr (predestination) and ḥadhar (precaution) by conducting a content analysis of his various texts. In this article, the authors mainly referred to his texts Sharaḥ Muslim, Riyaḍ al-Ṣāliḥīn, al-Majmūʿ Sharaḥ Muhadhdhab, Rawḍat al-Ṭālibīn and al- Adhkār al-Muntakhab. This study substantiates that in the view of al-Nawawī, Islam postulates a balanced position between taking precaution and faith in Allah’s decrees in dealing with the situations of an epidemic. Thus, it holistically complements the concepts of qadr and hadhar to guide people towards leading a faithful and safe life in the trying times of epidemic.